2016
DOI: 10.1097/md.0000000000003114
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width to Platelet Ratio is Related to Histologic Severity of Primary Biliary Cirrhosis

Abstract: We aimed to investigate whether red blood cell distribution width (RDW) and RDW to platelet ratio (RPR) were related to the histologic severity of primary biliary cirrhosis (PBC).Seventy-three treatment-naïve PBC patients who had undergone a liver biopsy between January 2010 and January 2015 were enrolled in our study. The patients’ histological stages were based on the classifications of Ludwig and Scheuer. The patients were divided into early stage (Stage I) and advanced stage (Stage II, III, and IV) hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 42 publications
0
42
0
Order By: Relevance
“…A new index, namely RPR, which possesses a good predictive property for inflammatory liver and cardiac diseases in adults, was put forth . General sterile inflammation was thought to have a part in PDA pathogenesis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A new index, namely RPR, which possesses a good predictive property for inflammatory liver and cardiac diseases in adults, was put forth . General sterile inflammation was thought to have a part in PDA pathogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…A new index, namely RPR, which possesses a good predictive property for inflammatory liver and cardiac diseases in adults, was put forth. [20][21][22] General sterile inflammation was thought to have a part in PDA pathogenesis. 26 This systemic inflammation was overt during the first 3 days of life independent of sepsis, probably due to intensive care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, markers obtained from or calculated using CBC indices, including RDW and/or RPR, were also considered as independent risk factors for studying liver diseases such as HBV-related diseases [8, 10, 1517], PBC [11], and NAFLD [18]. However, only a few studies in the literature have investigated the relationship between RDW, RPR, and PLR and hepatitis C.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,11,12 Study in primary biliary cirrhosis patients, the RDW/platelet ratio can predict liver fibrosis with 46.7% sensitivity and 96.4% specificity. 13 Another study also showed an increase in RDW was associated with the incidence of cardiovascular complications and increased mortality. 14 …”
Section: Introductionmentioning
confidence: 99%